2017
DOI: 10.1021/acs.inorgchem.7b00796
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical, Spectroscopic, and1O2Sensitization Characteristics of Synthetically Accessible Linear Tetrapyrrole Complexes of Palladium and Platinum

Abstract: The synthesis, electrochemistry, and photophysical characterization of a 10,10-dimethyl-5,15-bis(pentafluorophenyl)-biladiene (DMBil1) linear tetrapyrrole supporting PdII or PtII centers is presented. Both of these nonmacrocyclic tetrapyrrole platforms are robust and easily prepared via modular routes. X-ray diffraction experiments reveal that the Pd[DMBil1] and Pt-[DMBil1] complexes adopt similar structures and incorporate a single PdII and PtII center, respectively. Additionally, electrochemical experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(77 citation statements)
references
References 51 publications
11
66
0
Order By: Relevance
“…The emission properties of the Pd [ DMBil1 ] complex in nitrogen-saturated methanol are also largely unaffected by PEGylation. As has been previously observed for Pd- [ DMBil1 ], 15 excitation of Pd [ DMBil1 ] -PEG 750 with 500 nm light elicits weak fluorescence from 500 to 700 nm as well as phosphorescence from 700 to 850 nm (Figure 2). Table 1 shows that, while the fluorescence emission maximum of Pd [ DMBil1 ] -PEG 750 in methanol is red-shifted by 11 nm compared with that of Pd [ DMBil1 ], the fluorescence quantum yield of the PEGylated derivative ( Φ fl = 1.4 × 10 −4 ) is essentially identical to that of the parent compound ( Φ fl = 1.3 × 10 −4 ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The emission properties of the Pd [ DMBil1 ] complex in nitrogen-saturated methanol are also largely unaffected by PEGylation. As has been previously observed for Pd- [ DMBil1 ], 15 excitation of Pd [ DMBil1 ] -PEG 750 with 500 nm light elicits weak fluorescence from 500 to 700 nm as well as phosphorescence from 700 to 850 nm (Figure 2). Table 1 shows that, while the fluorescence emission maximum of Pd [ DMBil1 ] -PEG 750 in methanol is red-shifted by 11 nm compared with that of Pd [ DMBil1 ], the fluorescence quantum yield of the PEGylated derivative ( Φ fl = 1.4 × 10 −4 ) is essentially identical to that of the parent compound ( Φ fl = 1.3 × 10 −4 ).…”
Section: Resultssupporting
confidence: 81%
“…Pd [ DMBil1 ] -PEG 750 is readily accessible from unfunctionalized Pd [ DMBil1 ], which is readily prepared (Scheme 2) in four steps using methodology previously developed for the synthesis of biladienes 15,20 and related tetrapyrroles containing sp 3 hybridized meso -carbons. 2123 PEGylation of the parent Pd [ DMBil1 ] architecture was facilitated by the presence of the two pentafluorophenyl substituents at the 5- and 15-positions, which can be derivatized via nucleophilic aromatic substitution of the para -fluorine substituents.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated HOMO-LUMO energy gaps are 6.302 and 6.413 eV for the Ni and Pd complexes, respectively and reduced to 6.062 eV for the Pt complex, which is caused by a marked stabilisation of the LUMO (Figure 3). This series Pd > Ni > Pt agrees quite well with the experimental binding energies and electrochemical or optical HOMO-LUMO gaps of comparable series of Pt, Pd, and Ni complexes [63][64][65]67,77].…”
Section: Energies and Compositions Of The Frontier Orbitalssupporting
confidence: 85%
“…A shorter The calculated M-N bond lengths increase from 1.912 to 2.015 Å along the series Ni << Pt < Pd which reflects the size of the central atom (Tables S2-S4, Supplementary). In many experimental and theoretical studies, Pd II has been found slightly larger than Pt II [63][64][65][66][77][78][79][80][81], in keeping with the effects of the lanthanide contraction [82]. While for the Ni complex (Table S2) the two calculated M-N bonds show identical length, for Pd the M-N6(oximate) bond is slightly shorter than M-N3(oxime) (Table S3).…”
Section: Dft-optimised Molecular Geometriesmentioning
confidence: 64%
“…Pd[DMBil1]-PEG 750 was synthesized using methods described previously [ 28 , 38 , 39 , 40 , 41 ]. Reactions requiring an inert atmosphere were carried out in oven-dried round bottomed flasks fitted with Suba-seal rubber septa purchased from Chemglass and maintained under positive nitrogen pressure using standard schlenk techniques.…”
Section: Methodsmentioning
confidence: 99%